THE ROLE OF HYALURONIC ACID IN PERIODONTITIS THERAPY - Diana Roman; Irina Georgeta Șufaru; Liliana Păsărin; Lorena Roman; Silvia Teslaru; Iulia Săveanu; Gianina Iovan; Sorina Mihaela Solomon (Romanian Society of Oral Rehabilitation, 2023)
While scaling and root planing is an affordable strategy for treating periodontitis in its initial stages, it is unable to completely eliminate subgingival pathogens and to stop the loss of progressive attachment in certain cases. For some patients, the degree of clinical attachment gain and probing depth reduction offered by nonsurgical periodontal treatment might be enhanced by the supplementary administration of hyaluronic acid (HA) right after scaling and root planing is completed. This article analyzes the evidence for the effectiveness of HA, explores the justification for its prescription, and lists relevant practical concerns that should be considered when using HA as an adjunctive periodontal therapy. HA generates a variety of beneficial effects, including the enhancing of wound healing, in a manner which is similar to periodontal tissues. HA is already widely used in different medical fields and has exciting potential uses in dentistry. HA can be used as an adjunctive periodontal treatment for patients with gingivitis and periodontitis, greatly improving their quality of life in the process.